Recovery from cucumber mosaic virus infection for ‘Calwonder’ bell pepper plants does not counter negative impacts on plant growth - Murphy, John F.; Masiri, Jongkit; Hadi, Buyung A. R.; Dute, Roland R. (Wiley, 2016)
Cucumber mosaic virus (CMV) accumulation in leaves and stems of infected bell pepper plants at specific symptom stages was evaluated with an emphasis on the transition from full infection to recovery from Cucumber mosaic disease. Four symptom phases occurred in successive order, designated chlorosis (leaves 6–8), mosaic (leaves 9–11/12), leaf distortion (first series of leaves on secondary and tertiary branches) and recovery (progressive recovery with newly emerging leaves in tertiary and younger branches). In situ detection of CMV in leaf tissues revealed widespread occurrence in leaves expressing chlorosis and mosaic symptoms but reduced, localized occurrence in leaves in the recovery phase. Similarly, CMV accumulated to high levels throughout stems expressing chlorosis and mosaic symptoms but with dramatically reduced levels for plants in the recovery symptom phase. Stunting of internodes occurred at all locations above the inoculated leaves by the first expression of systemic symptoms, suggesting an impact on stem growth in response to initial virus invasion of young developing tissues of the stem. Despite the recovery from CMV infection, plant growth was negatively impacted early in the infection process and remained so through the course of the experiment.